Pengaruh Regulasi Diri Dan Efikasi Diri Terhadap Stress Akademik Mahasiswa - Nursabiila Alyaa Qonita; Dhea Aldalia; Siti Ayu Lestari; Lucky Purwantini (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Academic stress experienced by students can arise from various factors, such as competition for achievements, pressure to excel academically, high GPA demands, diverse coursework tasks, and the risk of dropping out. Efforts to address this academic stress involve self-regulation, including motivation to set life goals, designing action strategies, and self-efficacy to control activities and manage time efficiently, thereby assisting students in overcoming obstacles in the academic context. The subjects in this study are students at Universitas Islam 45 Bekasi. The research on the influence of self-regulation and self-efficacy on academic stress employs a quantitative method. The analysis of Pearson product-moment correlation indicates a significant negative relationship between self-regulation and academic stress. However, the results of the Pearson product-moment correlation show no significant relationship between self-efficacy and academic stress.